Ectopic abdominal pregnancy: Case reportedin Ambato (Ecuador) - Miranda Ruiz, Octavio (2015)
Ectopic pregnancy (EP) is the implantation of the fertilized egg outside the uterine cavity, its incidence has increased in recent decades. The abdominal EP is a rare form, located at the level of the peritoneal cavity outside the uterine cavity. For diagnostic criteria used Studdiford. It has ahigh maternal morbidity and mortality associated. We report the case of a patient 33 years old, married. Prior vaginal delivery and LMP uncertain, with irregular menstrual cycles, progestogen therapy for two months, and menstrual bleeding for 8 days during the last month. Enteres by emergency with signs of hypovolemic shock. Laparatomy was performed and confirmed diagnosis. Fetus and Annexes fetus and extracted with favorable evolution.